AKTIVITAS ANTIBAKTERI DAN ANTIOKSIDAN PEPTIDA SUSU KAMBING HASIL HIDROLISIS DENGAN PROTEASE LACTOBACILLUS PLANTARUM S31 - Herlina, Nina; Mustopa, Apon Zaenal; Surachma, Rahma Sari; Triratna, Lita; Kartina, Gina; Alfisyahrin, Wida Nurul (Perhimpunan Biologi Indonesia, 2019)
ABSTRACTResearch on the hydrolysis of milk with various protease obtained from the digestive tract, plants and animals has been widely carried out, but the hydrolysis process of goat milk with protease enzymes from Lactobacillus plantarum S31 isolated from bekasam is still widely unknown. This study aims to determine the antibacterial and antioxidant activity of peptides hydrolyzed by protease enzymes from L. plantarum S31. Isolation and purification of extracellular proteases was carried out with 80% ammonium sulfate saturation, dialysis and G50 Sephadex matrix. The results of hydrolysis showed that fraction 11 has the highest antioxidant activity. Goat milk with pH 5 has a greater inhibitory activity of about 29%, which is 5% compared to goat milk pH 7. This fraction also has a quite good antibacterial activity of Entero Phatogenic Escherichia coli (EPEC K1.1) bacteria, Staphylococcus aureus and Listeria monocytogenes. Keywords: goat milk, hydrolysis, antibacterial, antioxidant, Lactobacillus plantarum